Aplikasi Pengelolaan dan Pelaporan Kas RT/RW Berbasis Web di RT 005/03 Pejaten Barat - Firmansyah Surya Putra; Farizi Ilham; Ardi Hidayattuloh; Jihan Rifa Salwa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Cash management within the RT/RW community environment is an important activity in maintaining proper financial administration among residents. This activity includes recording cash inflows and outflows such as monthly contributions, community activity funds, and operational expenses. However, in practice, cash recording is still commonly performed manually using notebooks or simple spreadsheets that are not well integrated. This condition results in poorly organized financial data, risk of recording errors, and difficulties in searching data and preparing reports which require considerable time. The purpose of this Practical Work (KP) is to design and develop a web-based RT/RW Cash Management and Reporting Application to assist administrators in managing financial data effectively and efficiently. The system development method used is the Software Development Life Cycle (SDLC) with the Waterfall model, which includes requirement analysis, system design, implementation, and testing stages. The system was developed using PHP programming language and MySQL database. The system scope includes resident data management, cash inflow and outflow recording, monthly and annual reporting, cash information dashboard, data search features, and user management. The expected result of this application is to improve financial administration order, minimize recording errors, simplify report generation, and enhance transparency of cash management for residents.